Analysis Of Costumer Behavior To Achieve Target Users Of The New PLN Mobile Application Using Extended Utaut Model (Case Study: PT PLN UIW KALTIMRA) - Nanda Fathia Saputri; Bustanul Arifin Noer (Green Publisher Indonesia, 2024)
The New PLN Mobile is a mobile application developed by PT PLN (Persero) to help all customers in electricity-related activities. One of the PLN companies that uses Key Performance Index (KPI) to improve the performance of the New PLN Mobile application is PT PLN Unit Wilayah Kalimantan Timur – Utara (UIW KALTIMRA) with the aim of enhancing customer satisfaction. In this study, the analysis was carried out using the extended UTAUT (Unified Theory of Acceptance and Use of The Technology) model with PLS-SEM. The variables include performance expectancy, effort expectancy, social influence, facilitating conditions, trust, information quality, behavioral intention, use behavior, and customer satisfaction. The research involves 105 respondents who have used the New PLN Mobile and are located in the East Kalimantan or North Kalimantan region. There are 8 initial hypotheses and hypothesis testing will be carried out based on the questionnaire data processed in the extended UTAUT model. The results of hypothesis testing indicate that 5 hypotheses are accepted, and 3 hypotheses are rejected. The accepted hypothesis reveals that social influence and information quality have a positive and significant impact on behavioral intention; trust and behavioral intention have a positive and significant impact on use behavior; and use behavior has a positive and significant impact on customer satisfaction. The results of the study provide the basis for managerial implications for PT PLN UIW KALTIMRA. Six magerial implications have been formulated, with four impliactions responded to positively by the company and two implications that cannot be implemented in future.